A Durable Ni–Zn Microbattery with Ultrahigh‐Rate Capability Enabled by In Situ Reconstructed Nanoporous Nickel with Epitaxial Phase. Issue 42 (15th September 2021) - Zhu, Zhe; Kan, Ruyu; Wu, Peijie; Ma, Yao; Wang, Zhaoyang; Yu, Ruohan; Liao, Xiaobin; Wu, Jinsong; He, Liang; Hu, Song; Mai, Liqiang
Abstract: Powering device for miniaturized electronics is highly desired with well‐maintained capacity and high‐rate performance. Though Ni–Zn microbattery can meet the demand to some extent with intrinsic fast kinetic, it still suffers irreversible structure degradation due to the repeated lattice strain. Herein, a stable Ni–Zn microbattery with ultrahigh‐rate performance is rationally constructed through in situ electrochemical approaches, including the reconstruction of nanoporous nickel and the introduction of epitaxial Zn(OH)2 nanophase. With the enhanced ionic adsorption effect, the superior reactivity of the superficial nickel‐based nanostructure is well stabilized. Based on facile miniaturization and electrochemical techniques, the fabricated nickel microelectrode exhibits 63.8% capacity retention when the current density is 500 times folded, and the modified hydroxides contribute to the great stability of the porous structure (92% capacity retention after 10 000 cycles). Furthermore, when the constructed Ni–Zn microbattery is measured in a practical metric, excellent power density (320.17 mW cm −2 ) and stable fast‐charging performance (over 90% capacity retention in 3500 cycles) are obtained. This surface reconstruction strategy for nanostructure provides a new direction for the optimization of electrode structure and enriches high‐performance output units for integrated microelectronics. Abstract : Reconstructed nanoporous nickel with epitaxial Zn(OH)2 nanophase is designed to boost the activity and stability of the nickel cathode. With the facile electrochemical techniques and surface‐reconstruction strategy, excellent power density (320.17 mW cm −2 ) and stable fast‐charging performance (over 90% capacity retention in 3500 cycles) are obtained for Ni–Zn microbattery.